Implementation Trends of Cooperative Learning in Digital Learning Environments bibliometric approach - Judijanto, Loso (Eastasouth Institute, 2025)
This study provides a comprehensive bibliometric analysis of the trends and collaborations in cooperative learning within digital environments, focusing on how these pedagogical strategies are being integrated with technological advancements. Utilizing data from academic publications and conferences, the analysis identifies key contributors and highlights the role of the United States as a central hub in the research network. The findings reveal significant global collaborations and contributions from countries like Germany, the United Kingdom, and Malaysia, indicating a strong international interest in the field. The integration of digital technologies such as artificial intelligence and online platforms with cooperative learning strategies is emphasized, reflecting a shift towards more interactive and technologically enriched educational practices. The study discusses the implications of these trends for future educational methodologies and the importance of addressing challenges such as technological disparities and the effective implementation of digital tools in cooperative learning. The insights from this study are critical for educators, policymakers, and researchers aiming to enhance educational outcomes through innovative pedagogical practices.